A Gender Analysis of the Impact of Human Capital Development on Economic Growth in Nigeria - Chibuzor Happinessobi (African Governance and Development Institute (AGDI), 2023)
This study analysed the impact of education human capital development on economic growth in Nigeria from 1980 to 2020. The study specifically used secondary school enrolment as a comprehensive measure of education human capital, while life expectancy at birth was used as a measure of health human capital. By employing annual secondary time series data, the research aimed to assess the relationship between education human capital and economic growth in Nigeria. The data, obtained from the World Development Indicators of the World Bank, were subjected to appropriate descriptive and econometric techniques, including the Autoregressive Distributive Lag method. The findings revealed a significant positive correlation between education human capital development, as measured by secondary school enrolment, and economic growth in Nigeria. Therefore, the study recommends that government expenditures be directed towards human capital development, with a particular emphasis on education, to promote increased, sustainable, and equitable economic growth. In summary, this research highlights the importance of gender analysis in understanding the effects of human capital developments on economic growth in Nigeria. By recognizing the specific impact of education and health on economic growth, policymakers can make informed decisions to foster sustainable economic development.
Keywords: 330; Development; Economic growth; Gender; Human capital; Investment